Prospects for Expanding the Market for American Queen Bee in Europe and North America - Olshanskyi, Oleksandr (Академічні візії, 2025)
In the current conditions of global beekeeping development, the efficiency of beekeeping largely depends on the genetic characteristics of queen bees used in production. The queen bee market is influenced by global trends, including an ever-increasing demand for highly productive breeds, increased competition between exporting countries, and the need to ensure product quality. At the same time, the issue of importing American queen bees to Europe and North America requires a detailed analysis, in particular in the context of economic prospects, regulatory requirements, and potential challenges for local beekeeping. The importance of the study stems from the need to develop comprehensive measures to stabilize the market, support local producers and increase the efficiency of the beekeeping industry. The study is aimed at analyzing the prospects for expanding the market for American queen bees in Europe and North America, assessing the economic benefits of their use, and developing measures to create favorable conditions for the integration of imported queen bees into local beekeeping systems. The study uses a comprehensive approach that combines methods of economic analysis, comparative legal analysis, and expert evaluation. The analysis of regulatory aspects is based on a comparative study of EU, US and Canadian legislation on the import of bee products. The study showed that the use of American queen bees can help increase the productivity of local apiaries due to the high honey production of bees and their resistance to diseases. At the same time, market expansion requires comprehensive measures to regulate imports, including setting minimum prices for imported honey in line with production costs, introducing anti-dumping duties, strengthening product quality control, and creating a mandatory system for tracing the origin of honey. It is proposed to develop state programs to support local beekeepers, finance breeding initiatives and provide preferences for domestically produced products. The use of American queen bees in beekeeping in Europe and North America has significant potential to increase apiary productivity. However, the effective integration of such queens into local production systems requires government regulation, economic support for local producers, and market transparency. The implementation of the proposed measures will help to increase the competitiveness of the beekeeping industry, maintain its economic sustainability and ensure high quality products for end consumers.